1989
DOI: 10.1152/ajpregu.1989.256.3.r792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brain natriuretic peptide on renal nerve activity in conscious rabbits

Abstract: Responses of renal nerve activity (RNA) to intravenous infusion of brain natriuretic peptide (BNP) were examined in chronically instrumented conscious rabbits with all baroreflexes intact, sinoaortic baroreceptor denervation (SAD), and SAD plus vagotomy. In intact rabbits, an infusion of BNP at a rate of 0.3 microgram.kg-1.min-1 for 30 min decreased mean arterial pressure (MAP) by 8 +/- 1 mmHg and increased RNA by 48 +/- 4% but did not alter heart rate (HR). The decrease in MAP in SAD rabbits (20 +/- 3 mmHg) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…For CNP, the results are the first of their kind. Those with BNP support findings from the one previous report in rabbits (Morita et al 1989). The ANP results are similar to previous findings in rats (Woods et al 1994; Thomas et al 1997, 2002; Thomas & Woods, 2003) and humans (Ebert & Cowley, 1988).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For CNP, the results are the first of their kind. Those with BNP support findings from the one previous report in rabbits (Morita et al 1989). The ANP results are similar to previous findings in rats (Woods et al 1994; Thomas et al 1997, 2002; Thomas & Woods, 2003) and humans (Ebert & Cowley, 1988).…”
Section: Discussionsupporting
confidence: 91%
“…There is only one study of the effects of this peptide directly on arterial baroreflexes. Morita et al (1989), using drug‐induced changes in blood pressure, demonstrated that BNP did not alter sigmoid curves describing the mean arterial pressure–heart rate (MAP–HR) or MAP–renal sympathetic nerve activity relationships in conscious rabbits. To our knowledge there are no reports of the action CNP on arterial baroreflexes.…”
mentioning
confidence: 99%
“…In the VMAC trial, there was a net output of Ͼ1 L during a 24-hr period. Although one recent study failed to show a beneficial effect on diuresis with nesiritide in patients with CHF (12), previous pilot studies suggested the renal excretory effects of nesiritide are related to changes in both glomerular hemodynamics and tubular function (13,14). Importantly, administration of nesiritide did not result in a significant increase in serum creatinine in this pediatric population.…”
Section: Discussionmentioning
confidence: 79%
“…BNP also interacts with the autonomic nervous system and in experimental animals has been shown to decrease sympathetic outflow [5] although the role of BNP in central control of blood pressure is less clear. This potential interaction has not been studied in man although it is worth noting that ANP and BNP have similar haemodynamic effects in man [3,6] and are equipotent as agonists of the type A natriuretic peptide receptor [7].…”
Section: Discussionmentioning
confidence: 99%